Adaptive Yoga - Yang, Ingrid 1979- (Champaign, IL Human Kinetics, 2021)
"Adaptive Yoga is intended to teach yoga teachers and qualified healthcare professionals how individuals with chronic diseases and disabilities can maximize their yoga practice and recognize the healing and other benefits they can find with a consistent practice"--Provided by publisher.
Introduction -- Part I. Principles of Adapting Yoga -- Chapter 1. Yoga as Rehabilitation -- Chapter 2. How the Body Moves -- Part II. Adapting Yoga for Specific Disabilities -- Chapter 3. Low-Back Pain -- Chapter 4. Osteoarthritis of the Hip and Knee -- Chapter 5. Rheumatoid Arthritis -- Chapter 6. Lower-Extremity Amputation -- Chapter 7. Spinal Cord Injury -- Chapter 8. Parkinson's Disease -- Chapter 9. Stroke -- Chapter 10. Cerebral Palsy -- Chapter 11. Multiple Sclerosis -- Glossary -- References -- Index.
MS Salazar (Recommending faculty) AY2022-2023
Includes bibliographical references (pages 330-341).
Keywords: Yoga -- Therapeutic use